The effect of ascorbic acid on semen hyaluronidase activity and sperm characteristics in rams - Sonmez, M.; Tanyildizi, S. (Ecole Nationale Veterinaire Toulouse, 2008)
The effects of ascorbic acid on semen hyaluronidase activity and sperm characteristics in rams were investigated in this study. For this purpose, twelve rams were used. The animals were randomly divided into two groups of 6 as control and treatment groups. Ascorbic acid was intravenously administered at a dose of 10 mg/kg body weight once daily for three days. Semen samples were taken at 1, 2, 4, 8, 12, 24, 48 and 72 h after treatment and examined for hyaluronidase activity, level of ascorbic acid and sperm characteristics. The results showed that the use of ascorbic acid caused the significant increase in semen ascorbic acid level and decrease in hyaluronidase activity within 8 hours after treatment when compared to the control group. However, there was no significant difference in the sperm characteristics between the control and treated animals. In conclusion, although short-term administration of ascorbic acid did not have any effect on sperm characteristics, it caused a significant decrease in the semen hyaluronidase activity.
Keywords: ram; semen; ascorbic acid; hyaluronidase; sperm